Tuna, Moringa And Tempe As A High Energy, High Protein Gimbap Bite For Pregnant Women With Chronic Energy Deficiency - Wulandari, Catur Ima; Puspita, Theresia; Hadisuyitno, Juin (Journal of Local Therapy, 2024)
The problem with nutrition that occurs in mothers pregnant is Chronic Energy Deficiency (KEK). Intake of energy and protein in the mother pregnant classified low below 70% figure adequacy amounting to 52.6% and 52.2%. Treatment to overcome Chronic Energy Deficiency in Pregnant Women by giving additions food made from local tuna, moringa, and tempeh. Obtain formulation tuna , moringa and tempeh as gimbap bite for pregnant women with chronic energy deficiency. This study used type study experiment with design study design random complete (RAL) with treatment formulation of tuna, moringa and tempeh . Experiments carried out consist of three levels of treatment (50:30:20), (45:25:30), and (40:20:40). Amino Acid score was more than 100 and the NPU and VC values were ?70. Data on organoleptic properties were collected by organoleptic test using hedonic method and statistically analyzed using Friedman at the 95% confidence level (p=0,05). Gimbap tuna, moringa, and tempeh in 100 grams own content energy 190.4-192,6 kcal , protein 6.9-7.1 grams, fat 6.1-6.4 grams and carbohydrates 27.2-27,4 grams. Gimbap tuna, moringa, and tempeh were not difference significant color, aroma, taste, and texture (p>0,05). Gimbap with the proportion of tuna 45: Moringa 25: tempeh 35 contains 370,7 kcal , 13.4 grams of protein, 12.3 grams of fat, and 51.9 grams of carbohydrates meets 15,2% of the needs for energy and 21,9% of maternal protein requirements for pregnant women .